Development of innovative clean air suits to increase comfort and simultaneously decrease operating room infections - Abreu, Maria José (2017)
Comfort is a growing concern in medical textiles and specifically in medical clothing industry and must be considered when it’s necessary to develop new products. Specifically, in the surgical garment, gowns and clean air suits, is important to consider comfort as part of the requirements for any personal protective equipment or medical device, since the products are formulated to meet the primary requirement: the protection, according with the European standard EN 13795:2011+A1:2013: Surgical drapes, gowns and clean air suits, used as medical devices for patients, clini-cal staff and equipment. General requirements for manufacturers, processors and products, teste methods, performance requirements and performance levels. Measuring comfort is difficult and this paper shows how to quantify comfort parameters using a thermal manikin for this specific PPE. For this study was made a quantitative analysis on two new developed clean air suits. The results show that textile materials can provide a good comfort experience for the user and not com-promise their function as a barrier material against operating room infections. With this study was possible to ensure a clean air suit with good protection, comfort and ergonomics features with the right balance be-tween protection and comfort.